1996
DOI: 10.1111/j.1471-0528.1996.tb09882.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a risk of malignancy index based on serum CA125, ultrasound findings and menopausal status in the pre‐operative diagnosis of pelvic masses

Abstract: Objective To evaluate the ability of a risk of malignancy index (RMI), based on a serum CA125 level, ultrasound findings and menopausal status, to discriminate a benign from a malignant pelvic mass and to discriminate early stage (Figo Stage I) from Stages II, III and IV of ovarian cancer. Design A prospective study. Setting Department of Gynaecology, Trondheim University Hospital, Trondheim, Norway. Participants One hundred and seventy‐three women, 30 years or older, consecutively admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
217
5
18

Year Published

2000
2000
2019
2019

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 311 publications
(250 citation statements)
references
References 18 publications
(33 reference statements)
10
217
5
18
Order By: Relevance
“…Ideally patients with ovarian malignancy should be operated by a gynecologic oncologist or referred to a cancer center. However in practice, preoperative diagnosis of malignancy is not so easy (Tingulstad et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Ideally patients with ovarian malignancy should be operated by a gynecologic oncologist or referred to a cancer center. However in practice, preoperative diagnosis of malignancy is not so easy (Tingulstad et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…In comparison to Jacobs et al 12 , sensitivity was 78% vs 71% and specificity was 80% vs 83% . Sensitivity 78% vs 68% and specificity 80% vs 82% were found in comparison to Tingulstad et al 9 . In relation to third research of Morgante et al 10 sensitivity and specificity were found 78% vs 71% and 80% vs 87% respectively .These small variations may be acceptable .…”
Section: Discussionmentioning
confidence: 76%
“…Referral of all pelvic masses would create logistical problems. Instead, pelvic masses with a small chance of being malignant can be distinguished from malignant tumors by using the Risk of Malignancy Index (RMI) [21]. Only patients with a RMI above the cutoff-level should be referred or operated in the hospital of diagnosis by a consulting specialized gynecologist.…”
Section: Discussionmentioning
confidence: 99%